Can Synchronized Reading Improve Advanced Reading Abilities? A Classroom Action Research on the Neurological Impress Method - Amin, Asriani; Mumpuniarti, Mumpuniarti (Journal of Innovation and Research in Primary Education, 2025)
Advanced reading difficulties significantly impede elementary students' academic progress, necessitating effective interventions that address both cognitive and affective dimensions of literacy development. This study examined teacher implementation of the Neurological Impress Method (NIM) and its effectiveness in improving advanced reading abilities among fifth-grade students experiencing reading difficulties. A two-cycle classroom action research design following Kemmis and McTaggart's model was conducted with 13 fifth-grade students at SD A Sangatta Utara, Indonesia. Data collection employed mixed methods including pre-post reading assessments, structured observations, interviews, and behavioral coding. The NIM intervention involved synchronized oral reading sessions between teacher and students, with progressive modifications based on reflective analysis. Significant improvements emerged across all reading dimensions. Mean scores increased 53.8% from baseline (50.9) to post-intervention (78.3), with student mastery rising from 30.7% to 84.6%. Component analysis revealed gains in pronunciation accuracy (46.8%), reading precision (53.9%), comprehension (37.3%), and prosody (41.8%). Behavioral indicators demonstrated substantial increases in reading confidence, with voluntary participation rising from 15.4% to 76.9%. Unexpectedly, high-performing students also showed continued improvement, suggesting NIM's applicability beyond remedial contexts. The Neurological Impress Method effectively enhanced both reading competencies and affective dispositions, establishing it as a feasible, resource-efficient intervention for elementary reading instruction.